2023
DOI: 10.2166/h2oj.2023.059
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID-19 and natural disasters on water consumption across sectors: case studies of Barbados and Trinidad and Tobago

Abstract: In 2020, the COVID-19 pandemic added another layer of complexity to the already disruptive risk profiles of these countries. Understanding how these hazards, both individually and cumulatively, impact sectors, particularly essential sectors such as the water sector, is crucial to addressing current and future risks that the islands are likely to face. This paper examines the impact of the COVID-19 pandemic on water consumption while considering additional natural hazards which occurred concurrently in two Cari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Except for Trinidad and Tobago, all other SIDS in Table 3 are charged by volumetric consumption. The reasons for low water tariffs can be traced to Trinidad and Tobago's high level of state paternalism due to oil wealth, public protests over rate increases, and a failure to implement metering due to a weak political will [1,38,40]. Research has shown that if tariffs are set too low, there may be a lack of funds to invest in the maintenance and expansion of water infrastructure and it is difficult to manage water demand.…”
Section: Water Resources Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…Except for Trinidad and Tobago, all other SIDS in Table 3 are charged by volumetric consumption. The reasons for low water tariffs can be traced to Trinidad and Tobago's high level of state paternalism due to oil wealth, public protests over rate increases, and a failure to implement metering due to a weak political will [1,38,40]. Research has shown that if tariffs are set too low, there may be a lack of funds to invest in the maintenance and expansion of water infrastructure and it is difficult to manage water demand.…”
Section: Water Resources Managementmentioning
confidence: 99%
“…Robust data management tools to enable the preparation of accurate information for modelling and projections and to support planning and development aimed at improving water resource sustainability have been suggested [1]. To achieve this the institutional capacity for data generation must be strengthened.…”
Section: Plos Watermentioning
confidence: 99%
See 1 more Smart Citation